Call Center Mathematics - Koole, Ger; Singh, Ramanjeet (Gyan Management Journal, 2007)
Call Center Mathematics -A scientific method for understanding and improving contact centers explains all generic aspects of call and contact centers to advanced topics such as skill based routing and multi-channel environments. Ger Koole authors it This book is an essential guide to identifying,understanding; using and managng the call center management. The target audience for this book is a variety of professionals who is dedicated to improving call center performance. There are a total of 9 chapters covering just over 76 pages. All the chapters are again divided into different parts to make it effective. addition to the chapters the Glossary and Annotated bibliography has also added. In each sub part the author discusses different aspects related to call center mathematics and explains with the help of examples.